Motivation and Coaching Influence on Patient Safety with Responsive Culture at Hospital X, Bekasi - Indrawati Seska Kading; Tjipto Rini; MF Arrozie (Digital Innovation : International Journal of Management, 2025)
Patient safety is a fundamental component of healthcare quality and a key indicator of hospital performance. Ensuring its implementation requires not only technical competence but also psychological and organizational support. This study aims to analyze the effect of motivation and coaching on the implementation of patient safety among nurses, with responsive culture as a mediating variable at Hospital X, Bekasi. A quantitative approach was employed using a cross-sectional design. Data were collected from 162 nurses in inpatient units using a structured questionnaire and analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS) using SmartPLS software. The results showed that both motivation and coaching have significant direct effects on the implementation of patient safety. In addition, both variables significantly influence the development of responsive culture, which in turn also has a significant effect on patient safety. Responsive culture serves as a strong mediating factor, reinforcing the relationship between individual-level factors (motivation and coaching) and organizational safety outcomes. These findings indicate that motivated nurses who receive structured coaching within a responsive organizational environment are more likely to engage in safe practices. This study contributes to the growing evidence that human and cultural factors are critical in improving patient safety outcomes. It also provides practical recommendations for hospital leaders to focus on motivation strategies, coaching mechanisms, and cultural transformation to build safer healthcare systems. Future research is suggested to involve multiple institutions and integrate qualitative methods for deeper contextual understanding.